Penerapan Arsitektur Bioklimatik Pada Rumah Susun Sewa Di Kabupaten Bantaeng - Nurul Rezkiyah Wahyuningsih; Rahayu, Irma; Sam , Mukhlishah (The Department of Architecture, Faculty of Science and Technology, Alauddin Islamic University of Makassar, 2023)
Abstract_ Population density in Bantaeng Regency has grown over ten years. One solution to address the issue of the need for settlements in urban centers will greatly help Low-Income Communities (MBR) because jobs are not yet established or are still in contract status where they are still allowed to move from place to place or work. On the other hand, extreme climate change, which always changes every time, can cause problems with the environmental conditions where you live, especially the climate in the Bantaeng Regency area. This research aims to design rental flats in Bantaeng Regency by applying the Bioclimatic concept. The research method used was a survey, collecting primary data by means of field surveys/observations and interviews. Secondary data collection is collected from literature studies, journals or scientific works related to titles, books, reading materials related to titles, and other literature. Exploratory data in the form of the results of analysis of primary data and secondary data. The planning of rental flats in Bantaeng Regency is expected so that the building can respond to the surrounding climate and the occupants are comfortable living in the building by adopting bioclimatic architecture.